"ABSENTEE INFORMATION": Lucy R. Lippard's MoMA Library Intervention—From Decision to Stance. (1st June 2018) - Lauder, Adam
"Absentee Information, "Lucy R. Lippard's contribution to the iconic catalogue for INFORMATION(1970), the era-definingMoMA exhibition curated by KynastonMcShine, illuminates the informational and proto-feminist logics underpinning the innovative critic-curator's approach to problems of community decision amidst her transition to a feminist position. The contemporary "non-philosophy" of François Laruelle suggests a new path of approach to Lippard's instruction- and choice-based methodology as seizing upon contemporaneous manifestations of "digitality" in Conceptual art, but redescribing the tautological structures of mainstream conceptualism in emphatically situated terms—as a lived "stance." This article traces the sources of Lippard's library intervention, contextualizing "Absentee Information" within contemporaneous artistic, political and information-theoretic currents.